Analysis of Current Ratio (CR), Debt To Equity Ratio (DER), Total Asset Turnover (TATO), Return On Assets on Share Prices in Mining Companies - Dicky Tri Ganesha; Dayan Hakim Natigor Sipahutar; Yoyo Sudaryo; Nunung Ayu Sofiati (Green Publisher Indonesia, 2024)
The share prices of mining companies included in the LQ 45 Index are unstable because they experience increases and decreases from 2018 to 2023 (5 years). If the other independent variables remain constant, each increase is one unit Debt to Equity Ratio will reduce share prices -0.643. Then influence Total Asset Turnover to Share Prices in Mining Companies that are members of the LQ 45 Index for the 2018-2023 period is a significant and positive influence. If the other independent variables remain constant, each increase is one unit Total Asset Turnover will increase the share price by 0.453. Furthermore, the influence of ROA (Return On Asset) to Share Prices in Mining Companies that are members of the LQ 45 Index for the 2018-2023 period is a significant and negative effect. If the other independent variables remain constant, each increase is one unit Total Asset Turnover will lower the Share Price 1,060. and Current Ratio, Debt to Equity Ratio, Total Asset Turnover, ROA (Return On Asset) simultaneous significant effect on share prices in Mining Companies that are members of the LQ 45 Index for the 2018-2023 period with a percentage of 79% means that it is 79% Current Ratio, Debt to Equity RatiO,Total Asset Turnover and ROA (Return On Asset) to Stock Price and the rest 21% influenced by factor other than the variables studied.